Conservation choice on the rare endangered plants Glehnia littoralis. Issue 1 (29th January 2018) - Pan, Yanxia; Chu, Jianmin; Yang, Hongxiao
Abstract : Inland cultivation caused declines of buoyancy and germination ability of Glehnia littoralis fruits, because of long-term dispersal failure. Inland transplanting is, therefore, insufficient for conserving this species. As a coastal specialist, G. littoralis can only persist for long along sand coasts, where storm surge is a natural vector for dispersal. Abstract: The coastal herbs Glehnia littoralis have been domesticated as traditional medicines for many centuries. The domestication may have caused changes or declines of cultivated G. littoralis (CGL) relative to wild G. littoralis (WGL). By comparing fruit properties of CGL and WGL, we tested the hypothesis that domesticated G. littoralis have suffered major declines, and human cultivation cannot be sufficient to conserve this species. We collected fruits of CGL and WGL in the Shandong peninsula, China, and compared their buoyancy in seawater, germination potential after seawater immersion, and thousand-grain weights. Float rates of the WGL and CGL fruits were 95.6 (mean) ± 2.6% (standard deviation) and 30.0 ± 7.1%, respectively. The germination potential of CGL was significantly reduced, although the thousand-grain weights of CGL (21.85 ± 0.17 g) were higher than those of the WGL fruits (14.73 ± 0.21 g). These results suggest that the CGL have experienced significant declines relative to the WGL, presumably due to the loss of seawater inundation, selection and dispersal. These declines disfavour the persistence of CGL, and human domestication and cultivation are believed to be insufficient for conserving G. littoralis . Sand coasts where WGL still persists should be designated timely as nature reserves to conserve this species.